2016
DOI: 10.3390/nu8090572
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-Rich Extract from Plantaginis Semen Ameliorates Diabetic Retinal Injury in a Streptozotocin-Induced Diabetic Rat Model

Abstract: Plantaginis semen, the dried ripe seed of Plantago asiatica L. or Plantago depressa Willd. (Plantaginaceae), has been traditionally used to treat blurred vision in Asia. The aim of this work was to investigate the effect of plantaginis semen ethanol extract (PSEE) on the amelioration of diabetic retinopathy (DR) in streptozotocin (STZ)-diabetic rats. PSEE has abundant polyphenols with strong antioxidant activity. PSEE (100, 200 or 300 mg/kg) was oral administrated to the diabetic rats once daily consecutively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Journal of Diabetes Research to insulin, is the hallmark of type 2 diabetes mellitus (T2DM). Insulin resistance always results in damage to small blood vessels, especially diabetic retinopathy (DR) [34][35][36]. DR is one of the most common diabetic microvascular complications and is a leading cause of blindness.…”
mentioning
confidence: 99%
“…Journal of Diabetes Research to insulin, is the hallmark of type 2 diabetes mellitus (T2DM). Insulin resistance always results in damage to small blood vessels, especially diabetic retinopathy (DR) [34][35][36]. DR is one of the most common diabetic microvascular complications and is a leading cause of blindness.…”
mentioning
confidence: 99%
“…Consistent with these previous reports, in the present study, HUCB‐MNC treatment abrogated the increased expression of VEGF in bladders of diabetic rats 4 weeks after the induction of diabetes. Previous studies showed that retinal VEGF gene and protein expression increased significantly in diabetic rats . Furthermore, earlier data reported a permanent increase in renal VEGF gene expression after 3 weeks of diabetes but not in long‐term diabetes .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies showed that retinal VEGF gene and protein expression increased significantly in diabetic rats. 62,63 Furthermore, earlier data reported a permanent increase in renal VEGF gene expression after 3 weeks of diabetes but not in long-term diabetes. 64 Conversely, Jang et al 65 showed that HUCB-derived mesenchymal stem cells had beneficial effects on renal ischemia-reperfusion injury through humoral effects and the induction of VEGF secretion.…”
Section: Hucb-mncs May Exert Beneficial Effects On Contractions Inducmentioning
confidence: 97%
“…These latter 2 processes have also been implicated in increased retinal leukostasis. Systemic administration of AGEs leads directly to increased retinal leukostasis in mice [48], whereas various antioxidant therapies neutralize the diabetes-induced increase in leukostasis [14,61].…”
Section: Current Paradigm Of Leukocyte-induced Vascular Pathology Leamentioning
confidence: 99%